Competitive champions versus cooperative advocates - Alison Frances Rogers; Amy M Gullickson; Jean A King; Elizabeth McKinley (Journal of MultiDisciplinary Evaluation)
Background: Evaluation offers non-profit organizations an opportunity to improve their services, demonstrate achievements, and be accountable. The extant literature identifies individuals who can enhance the uptake of evaluation as evaluation champions. However, a paucity of detail is available regarding how to identify them and the support they require.